2013
DOI: 10.7150/ijms.5967
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Reactivity to Laboratory Stressors in Healthy Subjects: Influence of Gender and Family History of Cardiovascular Diseases

Abstract: Although laboratory stressor tests have been applied as a preliminary protocol in some cardiovascular studies, there is a lack of data comparing the pressor and chronotropic responses among the main stressor tests. Therefore, the aim of this study was to evaluate the variability in hemodynamic responsiveness to the main stressor tests, establish a hyperresponsiveness cutoff criterion and analyze the influence of gender and family history of cardiovascular diseases (CVDs) in healthy subjects. We examined hemody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
0
3
1
Order By: Relevance
“…We cannot offer explanation for decrease in WCT-SI in lean and opposite response in obese. Reactivity to mental and physical stress is shown to be influenced by gender [37]. However, in our study, similar gender distribution in all 3 BMI groups and also repeated measure analyses controlled for age and gender may have nullified the gender effect if any on the reactivity in these 3 groups.…”
Section: Baseline Hemodynamic and Autonomic Parameterscontrasting
confidence: 49%
“…We cannot offer explanation for decrease in WCT-SI in lean and opposite response in obese. Reactivity to mental and physical stress is shown to be influenced by gender [37]. However, in our study, similar gender distribution in all 3 BMI groups and also repeated measure analyses controlled for age and gender may have nullified the gender effect if any on the reactivity in these 3 groups.…”
Section: Baseline Hemodynamic and Autonomic Parameterscontrasting
confidence: 49%
“…Sex differences in BP responses during exercise. Females are reported to have lower BP responses compared with males during fixed duration relative-intensity static exercise (9,11,(14)(15)(16)38). Because maximal absolute load (MVC) is inversely related to static endurance (12), normalizing comparisons to a percentage of time to volitional failure has eliminated sex differences in BP responses in some (13,39,40) but not all studies (12,17).…”
Section: Discussionmentioning
confidence: 99%
“…The present study, as well as other research [ 9 ], announced a significant relationship between family of cardiovascular diseases and prehypertension risk. Laboratory stressor tests showed that healthy subjects with family history of cardiovascular diseases had a more positive hemodynamic responsiveness to stressor tests [ 72 ]. Our results demonstrated that smokers had 1.67 fold risks in getting prehypertension, while other researchers failed to report a significant relationship [ 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%